SISTEM PEMBAYARAN UPAH PEKERJA PADA HOME INDUSTRI BOLU IKAN DI KOTA LANGSA (Suatu Analisis Berdasarkan Ekonomi Islam) - febi febi; Ismail Fahmi Arrauf Nst; Muhammad Riza; Tri Novita (JIM: Jurnal Ilmiah Mahasiswa, 2019)
Wages are a form of compensation provided by business owners for workers. in terms of the owners, the wages are served as a guarantee for the continuity of production, while for workers the wages function to support their lives. The business owner must provide an appropriate wage for the work and the worker must work in accordance with the agreement. The problem occurs when there is no employment agreement was written on the division of labor, then the lazy workers with the diligent will get the same wage. In addition, the business owner must also ensure the wage that the worker will receive and when the employee will receive the wage. If there is no written agreement (contract), then the business owner may be fraudulent in terms of payment of wages. The purpose of this research is to find out how the process of determining the payment of wages of workers at “bolu ikan” home industry in Langsa and to analyze it based on Islamic economy. The type of research used is field study (field research) with qualitative descriptive approach. Primary data were obtained from interviews with business owners and workers at 5 “bolu ikan” home industry in Langsa, while secondary data was obtained through books, magazines, scientific papers and documents used to answer the problem of the research. The research concludes that the process of determining the payment of wages of workers at “bolu ikan” home industry in Langsa is not contradictory to the ruled of Islam, because there is a willingness of each party (mu'ajir and musta'jir). In this case, no workers feels persecuted. Each of them obtain a legitimate share of the product with it without being tyrannical towards the other and the fulfillment of the rights and obligations of each (business owner and worker).